Der GeoExplorer: ein Werkzeug für die Gestaltung ortsbezogener digitaler Lernerfahrungen - Kremer, Dominik; Feulner, Barbara; Wagner, Andreas (GW-Unterricht : eine Zeitschrift des "Forums GW - Verein für Geographie und Wirtschaftserziehung", 2025)
Lernen vor Ort fördert das Erschließen räumlicher Muster. Gleichzeitig liefern Geomedien am Standort Zusatzinformationen und ermöglichen den Vergleich einzelner Standorte. Der Aufwand für die Einarbeitung und Vorbereitung digital unterstützter Lernsituationen durch Apps ist weiterhin hoch. Am Beispiel der freien Anwendung GeoExplorer zeigen wir, wie eine gezielte Unterstützung des Eingabeprozesses nicht nur die Aufwände senkt, sondern auch die Vor-Ort-Erfahrung strukturiert, und stellen zwei Szenarien für den Einsatz an Schulen vo
Keywords: Mobiles ortsbezogenes Lernen; Exkursionen; (digitale) Geomedien; Co-Creation

Editorial - Digitale Geographiedidaktik außerschulischer Lernorte - Feulner, Barbara; Kremer, Dominik; Vogler, Robert (GW-Unterricht : eine Zeitschrift des "Forums GW - Verein für Geographie und Wirtschaftserziehung", 2025)

Exkursionsdidaktik innovativ - unterwegs mit i-Pad und Smartphone - Feulner, Barbara (Jenseits des Nürnberger Trichters - Ideen für einen zukunftsorientierten Geographieunterricht. Tagungsband zum 15. Bayerischen Schulgeographentag, 2012)

Rendering Cliché? Visual Consumption of Video Games as Virtual-Space Leisure Activities - Kremer, Dominik; Pappenberger-Muench, Naomi; Fuchs, Martin; Jelinski, Sarah; Feulner, Barbara; Walker, Blake (Gaming and Geography. A Multi-perspective Approach to Understanding the Impacts on Geography (Education), 2024)
As leisure activities, tourism and video games share the context of exploration and joy and serve the escapist fantasy. Drawing on theory of the respective field, we are able to identify even deeper similarities on how geographical space is produced by environmental storytelling and visual consumption in both cases. Both form hypergeographies highlighting only relevant fragments of space meant to provide convenience for the visitor during a stay. Can this congruence been shown by empirical analysis of gameplay and marketing materials? And how can these findings inform geo-education? In a mixed-method approach, we use digital walk-alongs to observe how players react on the identified categories during gameplay in selected games representing geographic space. In a second step, we show that marketing materials advertising tourist destinations and video games respectively also make congruent and intense use of the concepts identified. This comes at the risk that hegemonic structures known from tourism also apply to video games and can be made visible by counter-narratives from the Global South. Based on these findings, we propose to use the method asking pictures to teach students about the structural similarity and to reflect on the possible consequences.
CRIS-Team Scopus Importer:2024-10-04
Keywords: Socio-cultural framing; Tourism; Video games; Visual consumption